The impact of seed deficiency on productivity and on negative drought effect in semi‐natural grassland. (8th June 2020) - Stampfli, Andreas; Zeiter, Michaela
Abstract: Questions: Vegetative re‐sprouting and recruitment from seed determine grassland recovery after severe drought, but the mechanisms determining vegetation composition are not fully understood. We ask how the timing of drought and seed availability modify the drought legacy effects on composition and function in a temperate, semi‐natural grassland. Location: Negrentino, southern Alps, Switzerland. Methods: Under automated rainout shelters, we simulated extreme seasonal drought events in a late summer and in the following spring, added rainwater to simulate normal conditions in no‐drought controls and maintained haymaking at times of normal practice. Towards the end of the summer drought, we added seeds of ten local species in a three‐factor split‐plot arrangement with seven blocks as the replicated unit. We measured fine‐scale variation in soil depth. We assessed the biomass of graminoids and forbs at regular harvesting dates and the species frequencies of established plants and recruits before treatment start, repeating these assessments for three years thereafter. We measured the biomass proportions of post‐drought annual recruit cohorts in year 4 after drought. Results: One‐time seed addition augmented recruits, modified species composition and enhanced species diversity; these effects propagated to increased reproductive shoots of recruits and community biomass four years later. Single and repeated seasonal droughts only caused low adult plant mortality but clearly reduced recruitment from seed, while post‐drought establishment was slightly enhanced. Seed augmentation compensated the negative spring drought effect on forb recruits and in turn mitigated the negative impact of drought on species diversity after drought. Conclusions: Our experiment shows that seed deficiency limits productivity and that seed deficiency compensation can help to stabilize diversity and productivity in semi‐natural grassland. Releasing the current constraints of management on seed supply in grassland would therefore assist in mitigating negative drought impacts. Abstract : Is regeneration by seed required to maintain species richness and productivity in grasslands? Our experiment in semi‐natural grassland crossed seed addition with precipitation exclusion in summer and spring. We show that seed deficiency limits productivity, and seed augmentation compensates a negative effect of spring drought on species diversity. Enhancing the supply of local seeds would therefore assist in mitigating negative drought impacts.